Pengaruh Penerapan Kinerja Lingkungan, Biaya Lingkungan, Pengungkapan Lingkungan dan Ukuran Perusahaan Terhadap Profitabilitas Perusahaan Manufaktur Yang Terdaftar di BEI Tahun 2018-2022 - Nurul Fahira Hi Muhamad Saleh; Meliana; Zulkifli Abu (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2024)
This study aims to determine the effect of the application of environmental performance, environmental costs, environmental disclosure and company size on the profitability of manufacturing companies listed on the IDX in 2018-2022 This study uses quantitative methods using secondary data. Data collection techniques use purposive sampling techniques. The model used in this study is multiple linear regression using SPSS as an analysis tool. The results of hypothesis testing in this study show that environmental performance and environmental disclosure have no effect on profitability. Meanwhile, environmental costs and company size have a significant effect on profitability in manufacturing companies listed on the Indonesia Stock Exchange